The Human Element: Bureaucracy, Gender, and Race. (July 2015) - Box, Richard C.
Research on the people who deliver public services offers a useful alternative perspective in an applied field with an orientation toward organizational systems, performance, and accountability. It begins inside public organizations, treating public professionals as the subjects of research rather than objects to be controlled and manipulated. This essay reviews three new books that explore aspects of this alternative perspective, which we may call "the human element." These books focus on the characteristics of bureaucrats, women in the public sector, and race and social equity in government. They offer insights on difficult and controversial topics and serve as important resources for scholars and practitioners in public administration.